Macroscopic bubble generation promoted by nanobubble seeds as a traceless anti-fluctuation strategy for water splitting - Sheng Yang; Jing Yuan; Pengpeng Xie; Bo Li; Mengxuan Li; Daojin Zhou; Liang Luo; Xiaoming Sun (Nature Communications)
Abstract To adapt fluctuating renewable energy for water splitting is challenging, since the growth of electrochemically generated nanobubbles at early stage requires high supersaturation during the repeated start-stop cycles, which can accelerate the deactivation of electrodes and cause extra energy consumption. Herein, we propose a “bubble seeding” strategy by introducing nanobubbles (NBs, ~200 nm in diameter) into electrolyte to promote the generation of macroscopic bubbles. The precursive nanobubbles can act as the beforehand nuclei with a certain supersaturation, lower the supersaturation barrier for further growth, and result in reduced overpotential as high as 130 mV for oxygen evolution reaction. The enhancement depends on nanobubble coverage and size, with higher coverage and larger sizes favoring macrobubble growth. The nanobubbles with inert gas species (e.g. N2 for oxygen evolution reaction) can also work as the seeds, while the interfering or consumable gas species (e.g. O2 for hydrogen evolution reaction) would hinder the generation of macroscopic bubbles and enlarge the overpotential. The water splitting device working at presence of nanobubbles exhibits stable operation voltage during repeated start-stop cycles in contrast to traditional electrolyte without NBs, indicating great potential of such traceless nanobubble additive strategy for stabilizing gas evolution applications.